In-situ and Co-pyrolysis of Empty Fruit Bunch Fiber for Hydrocarbon Production - Bashar Hadi Abdullahi; Abdullahi Muhammad Sokoto; Aminu Bayawa Muhammad; Yahaya Alhassan; Chika Muhammad (Catalyx : Journal of Process Chemistry and Technology, 2024)
Significant amount of empty oil palm bunches are produced annually in Nigeria that mostly going to waste or as animal feed. This study explores the feasibility of transforming these bunches into hydrocarbons via pyrolysis process. The MoO3 and NiO catalyst materials   facilitated the catalytic pyrolysis resulting in favourable properties of EFB fibre pyrolysis products suitable for various applications. Valuable compounds were identified through GC-MS analysis of pyrolysis oils. In-situ catalytic pyrolysis with MoO3 and NiO catalysts favored acidic compounds, and produced combustible (CH4) and non-combustible (CO2) gases. Co-pyrolysis of Low-Density Polyethylene and the fiber generated high olefins and paraffin production, along with a significant 40% methane gas yield in both processes.  The study highlights the conversion potential of agricultural waste into valuable hydrocarbons, emphasizing the crucial role of catalysts with selectivity for acidic compounds and achieving high olefin, paraffin, and up to 40% methane gas yields in both co-pyrolysis and catalytic pyrolysis process.